ANALISIS STRATEGI GURU DALAM MENGAJARKAN SISWA MENYELESAIKAN SOAL CERITA MATEMATIKA PADA KELAS V SDN 09 TANJUNG LAY - Grafila, Ailen; Mastiah, Mastiah; M. Akip, M. Akip (STKIP Melawi, 2023)
This research is motivated by the difficulties of class V students at SDN 09 Tanjung Lay in solving math word problems. The research aims to determine the teacher's strategy in teaching students to solve math word problems in class V SDN 09 Tanjung Lay. The method in this study uses qualitative methods with a qualitative descriptive approach. The subjects in this study were class V teachers at SDN 09 Tanjung Lay. The object of this research is the teacher's strategy in teaching students to solve math word problems in class V SDN 09 Tanjung Lay. The research instrument uses interview sheets, observation sheets and documentation. Data collection techniques using interviews, observation and documentation. Data analysis techniques include data reduction, data presentation and conclusion. The validity of the data using triangulation techniques. The results showed that the teacher's strategy in teaching students to solve math word problems in class V SDN 09 Tanjung Lay was the strategy used by the teacher was quite good but the teacher's understanding of the learning strategy was slightly lacking. The strategies used by the teacher are motivating strategies, providing special guidance and using media related to learning. The method that the teacher uses is the lecture and discussion method with the technique of using real objects to provide understanding to students.